A Queueing Approach in Determining Optimal Numberof Beds in a Hospital Serving Urgent and Non-Urgent Patients - Abolnikov, L.; Zachariah, T.M. (Электронное моделирование, 2010)
In this paper, the authors consider a hospital as a multichannel queueing system that serves two different arriving Poisson flows of urgent and non-urgent customers (patients). The distribution of the service time is assumed to be exponential with different parameters for each kind of patients and priority for urgent patients. The results of the article are illustrated by several numerical examples obtained with the help of Mathematica program and can be easily applied to any hospital or its department. Рассмотрена больница как многоканальная система массового обслуживания, которая обслуживает два различных входящих пуассоновских потока: срочных и несрочных пользователей (пациентов). Распределение времени обслуживания экспоненциальное с различными параметрами для каждого вида пациентов и приоритетом в обслуживании срочных пациентов. Приведены численные примеры, выполненные с помощью программы Mathematica. Полученные результаты могут быть применены к любой больнице или ее отделениям. Розглянуто лікарню як багатоканальну систему масового обслуговування, яка обслуговує два різних вхідних пуасонівських потоки: термінових і нетермінових користувачів (пацієнтів). Розподіл часу обслуговування є експоненціальним з різними параметрами для кожного виду пацієнтів і пріоритетом в обслуговуванні термінових пацієнтів. Наведено числові приклади, виконані за допомогою програми Mathematika. Отримані результати можуть бути застосовані у будь-якій лікарні або ії відділеннях.